Implications of Bax, Fas, and p53 in the pathogenesis of early-stage mycosis fungoides and alterations in expression following photochemotherapy - Fatma Aydin; Yildiz Levent; Senturk Nilgun; Yuksel Esra Pancar; Turanli Ahmet Yasar (Wolters Kluwer Medknow Publications, 2011)
Background: The underlying molecular basis of mycosis fungoides (MF) has not yet been clarified. However, defects in apoptosis may contribute to its pathogenesis. Aim: We investigated the expression of Bax, Fas, and p53 in early-stage MF patients and any alterations in expression following photochemotherapy. Materials and Methods : Bax, Fas, and p53 expressions were studied by immunohistochemistry in both keratinocytes and lymphocytes on paraffin-embedded skin specimens from 27 early-stage MF patients. Results: Bax, Fas, and p53 staining was shown in the lymphocytes in 0/27, 26/27, and 11/27 patients at the time of diagnosis, whereas these ratios were 0/27, 9/27, and 0/27, respectively, after psoralen plus ultraviolet A (PUVA) treatment. The decrease in p53 and Fas expression in the lymphocytes was found statistically significant. Bax, Fas, and p53 staining in the keratinocytes was shown in 5/27, 27/27, and 25/27 patients at the time of diagnosis, whereas these ratios were 0/27, 22/27, and 4/27, respectively, after PUVA treatment. The decrease in p53, Fas, and Bax expression in the keratinocytes was found statistically significant. Conclusion: Although Bax seems unrelated with early-stage MF, Fas and p53 expression in the lymphocytes may contribute to the understanding of the pathogenesis of this disease.